2017
DOI: 10.3354/meps12125
|View full text |Cite
|
Sign up to set email alerts
|

Summer and fall distribution of phytoplankton in relation to environmental variables in Labrador fjords, with special emphasis on Phaeocystis pouchetii

Abstract: ). In autumn, the community was dominated by unidentified flagellates, prymnesiophytes and diatoms, in various proportions from early to late fall. From a summer situation characterized by stronger stratification, higher incident irradiance and depleted nutrients in surface waters, it evolved to an autumn situation characterized by decreasing air temperature and irradiance associated with an environmental forcing (e.g. weather) allowing cooling and greater vertical mixing of the water column. Combining our obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 92 publications
0
12
0
Order By: Relevance
“…4 a). None of the top autumn OTUs were diatoms, consistent with diatoms being limited by low autumn light availability and non-diatoms dominating under lower light conditions 21 . Autumn Chl a concentrations remained low in the surface and SCM, suggesting that the dinoflagellates were not overly reliant on photosynthesis.…”
Section: Discussionmentioning
confidence: 68%
“…4 a). None of the top autumn OTUs were diatoms, consistent with diatoms being limited by low autumn light availability and non-diatoms dominating under lower light conditions 21 . Autumn Chl a concentrations remained low in the surface and SCM, suggesting that the dinoflagellates were not overly reliant on photosynthesis.…”
Section: Discussionmentioning
confidence: 68%
“…Based on this novel pan-Arctic compilation, two main types of Arctic phytoplankton blooms were identified (occurring under both sea-ice-covered and sea-ice-free conditions; Figure 8), those dominated by diatoms and those dominated by the haptophyte Phaeocystis pouchetii (Figures 8 and 9). Phaeocystis pouchetii blooms have long been observed in the European Arctic sector (Smith et al, 1991;Schoemann et al, 2005) but have only recently been observed in Labrador fjords (Simo-Matchim et al, 2017) and Baffin Bay. Amongst these blooms, only one has been designated as an UIB (Assmy et al, 2017).…”
Section: Changing Nutriscapes and Icescapes Shape Phytoplankton Assemmentioning
confidence: 99%
“…The later station, located near the West Greenland coast, was also characterized by the presence of palmelloid colonial cells of Phaeocystis pouchetii, reaching 9 % of total cell count (0.5 × 10 6 cells L −1 ). Although the success and geographical range of Phaeocystis in the Northern Hemisphere are still poorly understood (Lovejoy et al, 2002;Schoemann et al, 2005;Tremblay et al, 2012), particularly in the Canadian Arctic, the codominance of species of Phaeocystis has been shown to occur in the waters of the West Greenland Current (Fragoso et al, 2017) and Labrador fjords (Simo-Matchim et al, 2017).…”
Section: The Myi Edge In Nares Strait and The Adjacent North Watermentioning
confidence: 99%
“…tion exposure with heightened DMS production as a defense strategy against light-associated oxidative stress (Sunda et al, 2002;Toole and Siegel, 2004;Vallina and Simó, 2017;Galí and Simó, 2010). The fresher water lens may also have indirectly stimulated DMS production through the possible enhancement of DMSP d availability and its bacterial conversion into DMS, following an osmosis-related excretion of cellular DMSP (Stefels, 2000;Van Bergeijk et al, 2003;Niki et al, 2007). Although biological processes cannot be completely ruled out, the strength of the association between DMS and salinity near the FYI edge suggests that physical drivers most strongly shaped DMS dynamics in Barrow Strait.…”
Section: Synthesismentioning
confidence: 99%